WAYS TO IMPRROVE ENVIRONMENTAL BRANDING - Чабан, Сергій; Павленко, Олена; Розмарина, Альбіна; Вітенчук, Катерина (SWorldJournal, 2022)
Ecological branding can affect the level of ecological comfort of society and stimulate the development of environmentally friendly goods and safe industries, so today this topic is very relevant. The purpose of this article is to study the theoretical a